THE RECOGNITION OF EXISTENCE AND BIBLICAL TRUTH IN THE PERSPECTIVE OF THE QUR'AN (Critical Study of the Development of Liberal Islamic Thought in Indonesia) - Setiawan, Asep (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2021)
This article seeks to highlight and provide answers to the controversial opinions that have recently been frequently campaigned by some liberal Muslim figures that the Qur'an recognizes the existence and truth of previous scriptures such as the Bible. They use several verses in the Qur'an, 5:44, 46-47 and 66, to justify the above opinions supported by partial interpretation experts under their understanding and purpose. In this study, the author used the library research method, which is research-based on library studies. The approach used is descriptive-analytical, which describes existing data sources, then analyzed and interpreted using available data sources. The opinion of liberal Islamic thinkers that it is enough for the Jews to use the Torah in carrying out religious law, and the Christians that they simply follow the rules in the Bible, this is because their methodology in understanding the verse is wrong. They did not explain at all the abuses committed by Jews and Christians. Including their defiance of Allah's command and about the guidance of the coming of the Prophet Muhammad with his perfect and universal sharia, which they are obliged to follow and obey, which is the information contained in their holy book. In understanding the verses of the Qur'an, they do not use methodological steps that can be accounted for in the discipline of interpretation. Contextual schools are emphasized for several texts that are alleged to be anti-religious pluralism. While on the other hand, literal schools are applied to verses that support the notion of religious pluralism. Artikel ini berupaya untuk mengetengahkan dan memberikan jawaban atas pendapat kontroversial yang belakangan ini sering dikampanyekan oleh beberapa tokoh muslim liberal bahwa al-Qur’an mengakui eksistensi dan kebenaran kitab suci sebelumnya seperti Bibel. Mereka menggunakan beberapa ayat dalam QS. Al-Ma’idah [5]: 44, 46-47, dan ayat ke-66 untuk menjustifikasi pendapat di atas didukung dengan menukil pendapat dari para ahli tafsir secara parsial sesuai dengan paham dan tujuan mereka. Pada penelitian ini, penulis menggunakan metode library research, yakni penelitian yang didasarkan pada studi pustaka. Adapun pendekatan yang digunakan adalah deskriptif-analitis, yaitu mendeskripsikan sumber data yang ada, kemudian dianalisis dan diinterpretasikan dengan menggunakan sumber data yang tersedia. Pendapat para pemikir Islam liberal bahwa kaum Yahudi cukup berhukum dengan Taurat begitu pula kaum Nasrani, yang katanya cukup berhukum dengan Injil atau Bibel, dikarenakan mereka cacat secara metodologis dalam memahami ayat tersebut. Mereka sama sekali tidak menerangkan tentang penyelewengan yang dilakukan orang-orang Yahudi dan Nasrani. Termasuk tentang pembangkangan mereka terhadap perintah Allah dan tentang petunjuk akan datangnya Nabi Muhammad saw. dengan syariatnya yang sempurna dan universal yang wajib diikuti dan ditaati oleh mereka, yang mana informasi tersebut terdapat di dalam kitab mereka. Dalam memahami ayat-ayat al-Quran, mereka tidak menggunakan ukuran metodologis yang dapat dipertanggungjawabkan secara disiplin ilmu tafsir. Mazhab kontekstual ditekankan untuk sejumlah teks yang diduga anti kemajemukan beragama. Sementara di sisi lain, mazhab literal diterapkan untuk ayat-ayat yang mendukung paham pluralism agama.